Pollination of the broad bean (Vicia faba L.var. major) (Fabaceae) by wild bees and honey bees (Hymenoptera: Apoidea) and its impact on the seed production in the Tizi-Ouzou area (Algeria) - Aouar-sadli, Malika; Louadi, Kamel; Doumandji, Salah-Eddine (Global Journal of Food and Agribusiness Management, 2018)
An experiment conducted with caged plots confirmed the large seed yield of Vicia faba L. in the presence of pollinating insects during the flowering season of the year 2003. The plants that were accessible to pollinators provided more pods per plant, more seeds per pods; the pods were longer and the seeds were heavier than the encaged plants. Among the pollinating insects of Vicia faba, in the Tizi Ouzou area (Algeria), the wild bee Eucera pulveracea Dours was the most abundant and seemed to be the most effective pollinator. His visits were all able to fertilize the flowers. On the contrary, several floral visits of the honey bee Apis mellifera L. and all visits of Xylocopa violacea were “nectar robbery” through the holes made by the bumblebees at the base of the corolla. The floral visits of Eucera pulveracea L. were also faster (10 visits per minute)